Neopomacentrus cyanomos (Pomacentridae), an IndoPacific reef fish at Aruba and Curaçao, southern Caribbean - Robertson, D Ross (2026)
In 2021, groups of the Indo-Pacific damselfish Neopomacentrus cyanomos were observed on reefs in Aruba, in the southern Caribbean. In 2016, a floating accommodation platform (flotel) used to support offshore petroleum extraction was towed from the southwestern Gulf of Mexico, where the damselfish was widespread and had been recorded on other petroleum platforms, first to Aruba and then to nearby Curaçao. In 2025, this study aimed to investigate whether the flotel transported N. cyanomos to those two islands. Previously published underwater videos of the submerged flotel hull, recorded in Curaçao in early 2017, were reviewed. In 2025, an information request was posted on social media for sightings of the damselfish in Curaçao. The 2017 videos showed many N. cyanomos living on the underside of the flotel that permanently left Curaçao in August 2017. In 2025, adult N. cyanomos were recorded living under a dock in Curaçao, and in 2026, they were replaced by two small fish. These are the most recent sightings of that species in Curaçao. The detection of N. cyanomos on the flotel in 2017 in Curaçao, followed by the sightings on the reefs of both islands, five and eight years after the platform passed by Aruba and Curaçao, provides evidence that the species was likely transported via the flotel, resulting in the establishment of a population, at least in Aruba.